2021
DOI: 10.1111/1758-2229.12986
|View full text |Cite
|
Sign up to set email alerts
|

Genome analysis of Streptomyces sp. UH6 revealed the presence of potential chitinolytic machinery crucial for chitosan production

Abstract: Summary Chitosan and its derivatives have numerous applications in wastewater treatment as bio‐coagulants, flocculants and bio‐adsorbents against both particulate and dissolved pollutants. Chitinolytic bacteria secrete an array of enzymes, which play crucial role in chitin to chitosan conversion. Consequently, there is a growing demand for identification and characterization of novel bacterial isolates with potential implications in chitosan production. We describe genomic features of the new isolate Streptomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…Chitin is the second-most abundant biosynthetic bio-polysaccharide after cellulose and is found in large quantities in shrimp and crab seafood waste ( Zhang et al, 2020 ). Most of these wastes are burned or dumped in coastal areas, causing environmental problems such as water pollution ( Duhsaki et al, 2022 ). Chitin and its derivatives are widely used in biomedicine, cosmetic refinement, food, and agriculture.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chitin is the second-most abundant biosynthetic bio-polysaccharide after cellulose and is found in large quantities in shrimp and crab seafood waste ( Zhang et al, 2020 ). Most of these wastes are burned or dumped in coastal areas, causing environmental problems such as water pollution ( Duhsaki et al, 2022 ). Chitin and its derivatives are widely used in biomedicine, cosmetic refinement, food, and agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, industrial enzymes face a major challenge in terms of stability, efficiency, and cost of their application ( Nakagawa et al, 2013 ; Liaqat and Eltem, 2018 ). Microorganisms degrade and/or modify chitin in nature by using a series of synergistically acting chitinolytic enzymes ( Duhsaki et al, 2022 ). Mining novel, highly efficient chitin-degrading enzymes from natural environments will lay a solid foundation for the industrial production of COS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the issue also has articles from scientists, utilizing genomic information for deciphering novel microbial resources. Duhsaki et al (2021) identified chitinolytic enzymes from the genome analysis of Streptomyces sp. UH6 for chitosan production, therefore having industrial applications.…”
mentioning
confidence: 99%
“…Duhsaki et al . (2021) identified chitinolytic enzymes from the genome analysis of Streptomyces sp. UH6 for chitosan production, therefore having industrial applications.…”
mentioning
confidence: 99%